Harnessing Poly(ionic liquid)s for Sensing Applications. Issue 14 (19th May 2016) - Guterman, Ryan; Ambrogi, Martina; Yuan, Jiayin
Abstract : The interest in poly(ionic liquid)s for sensing applications is derived from their strong interactions to a variety of analytes. By combining the desirable mechanical properties of polymers with the physical and chemical properties of ILs, new materials can be created. The tunable nature of both ionic liquids and polymers allows for incredible diversity, which is exemplified in their broad applicability. In this article we examine the new field of poly(ionic liquid) sensors by providing a detailed look at the current state‐of‐the‐art sensing devices for solvents, gases, biomolecules, pH, and anions. Abstract : Poly(ionic liquid)‐derived functional materials and devices for sensing applications have emerged as a new field that grows rapidly. Diversity in chemistry and physics of ionic liquids are nicely coupled with the excellent processability and multivalency of polymers, allowing for task‐specific detection of solvents, gases, biomolecules, pH, and anions.